2018
DOI: 10.1177/2325967118755048
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopic Surgery for Femoroacetabular Impingement: A Prospective Analysis of the Relationship Between Surgeon Experience and Patient Outcomes

Abstract: Background:Hip arthroscopic surgery is a rapidly growing procedure, but it may be associated with a steep learning curve. Few studies have used patient-reported outcome (PRO) surveys to investigate the relationship between surgeon experience and patient outcomes after the arthroscopic treatment of femoroacetabular impingement (FAI).Hypothesis:Patients undergoing hip arthroscopic surgery for the treatment of FAI in the early stages of a surgeon’s career will have significantly worse outcomes and longer procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
(64 reference statements)
0
25
1
Order By: Relevance
“…Another previous study found decreasing procedure and traction times after a surgeon’s first 30 cases. 11 However, the current study found that procedure and traction time decreased in a logarithmic curve, reaching a plateau after 70 and 110 cases, respectively. The procedure time plateaued before traction time, which indicates that efficiency in joint access and intra-articular labral repair needed for traction time proficiency takes longer to master compared with other aspects of the case that factor into the procedure time including patient setup, which can be time-consuming for hip arthroscopic surgery.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Another previous study found decreasing procedure and traction times after a surgeon’s first 30 cases. 11 However, the current study found that procedure and traction time decreased in a logarithmic curve, reaching a plateau after 70 and 110 cases, respectively. The procedure time plateaued before traction time, which indicates that efficiency in joint access and intra-articular labral repair needed for traction time proficiency takes longer to master compared with other aspects of the case that factor into the procedure time including patient setup, which can be time-consuming for hip arthroscopic surgery.…”
Section: Discussioncontrasting
confidence: 59%
“…These results were using 1-year outcomes and a small cohort size. 11 These findings are in contrast to a prospective study of a single surgeon’s first 100 hip arthroscopic procedures by Konan et al, 16 which showed the highest patient satisfaction and improvement in postoperative Non-Arthritic Hip Score values in the past 30 patients compared with the first 30. The authors also noted a 40% decrease in operative time after the first 30 cases, leading them to quantify a learning curve of 30 cases.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…34 The median MINORS score for the noncomparative studies in this review was 7 (range, 5-9). The median MINORS score for the comparative studies in this review was 12 (range, [10][11][12][13][14][15][16][17][18][19]. Overall, all studies had a clearly stated aim, 82.1% had appropriate endpoints, 67.9% had an appropriate follow-up period, and 75% had loss of follow-up less than 5%.…”
Section: Study Qualitymentioning
confidence: 99%
“…10,28,36 Three studies found significant improvement only in specific cohorts or in 1 subset of the SF-12 score. 15,27,29 The remaining 3 studies did not report significance values for postoperative SF-12 score improvement. 4,49,52 Of the 3 studies that found significant improvement in all cohorts, 1 was at follow-up between 12 and 24 months postoperatively, 10 1 between 25 months and 5 years, 28 and the last at greater than 5 years.…”
Section: Sf-12mentioning
confidence: 99%